Ranking the Harm of Psychoactive Drugs Including Prescription Analgesics to Users and Others–A Perspective of German Addiction Medicine Experts - Bonnet, Udo; Specka, Michael; Soyka, Michael; Alberti, Thomas; Bender, Stefan; Grigoleit, Torsten; Hermle, Leopold; Hilger, Jörg; Hillemacher, Thomas; Kuhlmann, Thomas; Kuhn, Jens; Luckhaus, Christian; et al. (Frontiers in Psychiatry, 2020)
Background: Over the past 15 years, comparative assessments of psychoactive substance harms to both users and others have been compiled by addiction experts. None of these rankings however have included synthetic cannabinoids or non-opioid prescription analgesics (NOAs, e.g., gabapentinoids) despite evidence of increasing recreational use. We present here an updated assessment by German addiction medicine experts, considering changing Western consumption trends–including those of NOAs. Methods: In an initial survey, 101 German addiction medicine physicians evaluated both physical and psychosocial harms (in 5 dimensions) of 33 psychoactive substances including opioids and NOAs, to both users and others. In a second survey, 36 addiction medicine physicians estimated the relative weight of each health and social harm dimension to determine the overall harm rank of an individual substance. We compared our ranking with the most recent European assessment from 2014. Results: Illicit drugs such as methamphetamine, heroin, cocaine and also alcohol were judged particularly harmful, and new psychoactive drugs (cathinones, synthetic cannabinoids) were ranked among the most harmful substances. Cannabis was ranked in the midrange, on par with benzodiazepines and ketamine—somewhat more favorable compared to the last European survey. Prescribed drugs including opioids (in contrast to the USA, Canada, and Australia) were judged less harmful. NOAs were at the bottom end of the ranking. Conclusion: In Germany, alcohol and illicit drugs (including new psychoactive substances) continue to rank among the most harmful addictive substances in contrast to prescribed agents including opioid analgesics and NOAs. Current laws are incongruent with these harm rankings. This study is the first of its kind to include comparative harm rankings of several novel abused substances, both licit/prescribed and illicit.